Unravelling textiles a handbook for the preservation oftextile collections - Boersma, Foekje; Brokerhof, Agnes W.; Berg, Saskia van den; Tegelaers, Judith (London Archetype Publications for the Netherlands Textile Committee, 2007)
It provides an invaluable source of study for textile conservation students and a useful aide-memoire for experienced textile conservators. It will also be of particular interest to non-text i le conservators who may have textiles in their care. The information it contains is orientated towards conditions found in temperate climates, but much of it is relevant to textile collections anywhere in the world. It could be a particularly useful resource for museums in developing countries. There are very few books on the subject of preventive conservation for textile collections, and there is nothing comparable that offers such a range of detailed information and advice in one volume. The twelve chapters in this book cover three areas. Chapters 1 to 5 describe the common fibres, their production, basic methods of textile manufacture and the processes of degradation. Chapters 6 to 9 discuss practical issues of textiles in storage, in transit and on exhibition and give advice on materials that are safe to use with textiles. Chapters 10 to 12 look at documentation, conservation and restoration issues and collection management. The book offers sound and thorough information on many aspects of important areas that form the foundation of modern collection care. Overall it has a good balance between theory and practical advice on a wide range of basic but essential practices and procedures.
Materials -- Degradation of textiles -- The museum environment -- Light -- Insects and fungi in textile collections -- Storage -- Transportation -- Textiles on display -- Materials for conservation -- Conservation and restoration -- Documentation -- Collection management.
"Translated from Dutch. First published in 2000 as Op de keper beschouwd: Handboek voor hetbehoud van textielcollecties by Stichting Textielcommissie Nederland" -- T.p. verso
Includes bibliographical references and index.
Keywords: Textile fabrics -- Collection and preservation; Textile fabrics -- Conservation and restoration